SISTEM PEMBELAJARAN DIGITAL INTERAKTIF (SIPEMBERANI) MENDUKUNG PEMBELAJARAN ONLINE DI SEKOLAH MENENGAH DI KOTA PALU - Lamasitudju, Chairunnisa Ar; Miftah, Miftah; Makmur, Elfira; Nuridayanti, Nuridayanti (ScientiCO : Computer Science and Informatics Journal, 2021)
Today's learning is one proof that civilization is increasingly sophisticated, but many still use conventional learning systems so that it limits the space for expressing the knowledge to be transferred. The outbreak of the Corona Virus Disease 19 (COVID 19) has also changed the learning system in Indonesia, especially in Palu City, which currently is conducting by full-time online learning system. Changes in the system have made it difficult for some subject teachers to adapt. This research designs an interactive digital learning system (Simberani) to support online-based distance learning during the Covid 19 pandemic. Sipemberani adopts the ADDIE (Analysis, Design, Develop, Implement, Evaluate) model and has tested where the system built is very helpful in online learning during a pandemic. It is proven from the results of a survey conducted that "87%" agree with this system.